One step forward, two steps back. U.S. relations with Cuba under Presidents Obama and Trump - Bodemer, Klaus (2020)
Since Fidel Castro’s triumph in Cuba in 1959, relations between the United States and the Caribbean island have been characterized by a high level of hostility and conflict for more than half a century. That changed during Barak Obama’s second term with a series of measures that seemed to signal the beginning of a new era of cooperation between the two countries. This strategy of thawing bilateral relations ended, however, with the electoral victory of Donald Trump and his favourite strategy “America first”. In order to satisfy his supporters, among them the Cuban exiles in the state of Florida, Trump reversed step by step a large part of his predecessor’s policy of openness with negative economic effects both for Cubans and, although less so, for American companies and citizens, and substantially worsened the image of the United States and its government both in the region and in Europe. A generational change in the Cuban community in Miami, protests from the European Union and from certain economic sectors in EEUU have also raised doubts as to whether the Trump administration’s rigid policy of sanctions will really survive the next elections in the United States in 2020. From the analytical point of view, we use approaches from neo-realism, social-constructivism and intermestic poltics.